A Seamless Technology Integration Framework for Elderly-Centered Interactive Systems: Design, Implementation, and Validation Through the Pillow Fight System - Lim, Chor-Kheng; Chen, Hung-Yu; Chen, Xuan-Yu (Applied sciences, 2024)
The rapid aging of the global population has highlighted the urgent need for age-friendly technological solutions. However, our review of the existing studies revealed significant gaps between elderly users’ needs and the current smart technology products. While previous research has explored various aspects of elderly technology design, our systematic analysis indicated limitations, in terms of integrated frameworks, empirically validated interaction models, and long-term effectiveness evaluation. This study proposes a seamless technology framework for the development of elderly-centered interactive systems—named Pillow Fight—which we validated through a mixed-methods study of an innovative intergenerational gaming system. This research was conducted in two phases across 34 sites, with 1997 participants. Phase one (n = 659) established the framework’s effectiveness through systematic field testing, while phase two (n = 1338) validated its scalability and long-term benefits. The results highlight significant improvements in system usability scores (SUS), from individual use (77.85) to group activities (85.32), with intergenerational interaction achieving the highest scores (92.12). The integration of health monitoring features further enhanced learnability (94.12) usability (82.15). This study contributes to the design of technology for the elderly through (1) establishing an integrated theoretical framework for seamless technology integration, (2) developing and validating innovative intergenerational interaction models, and (3) providing empirical evidence through systematic field studies. These contributions could advance both theoretical understanding and practical applications while maintaining high user-friendliness.